2004
DOI: 10.1074/jbc.m403809200
|View full text |Cite
|
Sign up to set email alerts
|

The Met Receptor and α6β4 Integrin Can Function Independently to Promote Carcinoma Invasion

Abstract: It has been proposed that a constitutive, physical association of the Met receptor and the ␣ 6 ␤ 4 integrin exists on the surface of invasive carcinoma cells and that hepatocyte growth factor (HGF)-mediated invasion is dependent on ␣ 6 ␤ 4 (Trusolino, L., Bertotti, A., and Comoglio, P. M. (2001) Cell 107, 643-654). The potential significance of these results prompted us to re-examine this hypothesis. Using three different carcinoma cell lines that express both Met and ␣ 6 ␤ 4 , we were unable to detect the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 28 publications
(36 reference statements)
2
46
0
Order By: Relevance
“…Previous studies have suggested that c-Met and laminin integrins may interact to regulate invasion (Trusolino et al, 2001;Chung et al, 2004). Our studies found that PC3 cells express higher levels of c-Met relative to DU145 cells and integrins were incapable of activating c-Met in DU145 cells.…”
Section: Discussionsupporting
confidence: 51%
“…Previous studies have suggested that c-Met and laminin integrins may interact to regulate invasion (Trusolino et al, 2001;Chung et al, 2004). Our studies found that PC3 cells express higher levels of c-Met relative to DU145 cells and integrins were incapable of activating c-Met in DU145 cells.…”
Section: Discussionsupporting
confidence: 51%
“…35,36 c-Met is known to cooperate with integrin a6b4 to enhance the migratory and invasive potential of cancer cells in vitro. 37,38 Furthermore, the tumorigenic potential of c-Met in cancer cells in vitro has been attributed to its cooperation with the integrin a6b4. 39 The integrin a6b4 has also been shown to promote the signaling of transcription factors such as NFAT-1 in carcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the loss of function of h 4 integrin signaling, we used RNA interference to block the expression of h 4 subunit as previously described (21). We first analyzed the expression of h 4 integrin subunit upon shRNA interference.…”
Section: Resultsmentioning
confidence: 99%
“…NIH3T3 cells were maintained in DMEM supplemented with 10% FCS. The inactivation of h 4 was obtained by LipofectAMINE PLUS method (Invitrogen) using pSUPER.retro vector containing h 4 -shRNA or a scramble RNA (scr-shRNA) sequences as previously described (21). Selection of puromycin-positive cells was carried out using 500 Ag/mL puromycin (Sigma, Milan, Italy).…”
Section: Methodsmentioning
confidence: 99%